Insomnia symptoms and behavioural health symptoms in veterans 1 year after traumatic brain injury. (15th October 2015) - Farrell-Carnahan, Leah; Barnett, Scott; Lamberty, Gregory; Hammond, Flora M.; Kretzmer, Tracy S.; Franke, Laura M.; Geiss, Meghan; Howe, Laura; Nakase-Richardson, Risa
Abstract: Objective : Insomnia and behavioural health symptoms 1 year after traumatic brain injury (TBI) were examined in a clinical sample representative of veterans who received inpatient treatment for TBI-related issues within the Veterans Health Administration. Methods : This was a cross-sectional sub-study ( n = 112) of the Polytrauma Rehabilitation Centres' traumatic brain injury model system programme. Prevalence estimates of insomnia, depression, general anxiety, nightmares, headache and substance use, stratified by injury severity, were derived. Univariate logistic regression was used to examine unadjusted effects for each behavioural health problem and insomnia by injury severity. Results : Participants were primarily male, < 30 years old and high school educated. Twenty-nine per cent met study criteria for insomnia; those with mild TBI were significantly more likely to meet criteria (43%) than those with moderate/severe TBI (22%), χ 2 (1, n = 112) = 5.088, p ≤ 0.05. Univariable logistic regression analyses revealed depressive symptoms and general anxiety were significantly associated with insomnia symptoms after TBI of any severity. Headache and binge drinking were significantly inversely related to insomnia symptoms after moderate/severe TBI, but not MTBI. Conclusions : Veterans with history of TBI, of any severity, and current insomnia symptoms may be at increased risk for depression and anxiety 1 year after TBI.